2007
DOI: 10.1021/la702411n
|View full text |Cite
|
Sign up to set email alerts
|

Co-sensitization of Organic Dyes for Efficient Ionic Liquid Electrolyte-Based Dye-Sensitized Solar Cells

Abstract: The co-sensitization of two organic dyes (SQ1 and JK2), which are complementary in their spectral responses, shows enhanced photovoltaic performance compared with that of an individual organic dye-sensitized solar cell. The power conversion efficiency of the co-sensitized organic dye solar cell based on the newly developed binary ionic liquid (solvent-free) electrolyte gives 6.4% under AM 1.5 sunlight at 100 mW/cm2 irradiation, which is higher than that of individual dye-sensitized solar cells. The incident mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
129
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(132 citation statements)
references
References 36 publications
0
129
0
3
Order By: Relevance
“…The conversion of sunlight to electricity using dye-sensitized solar cells (DSCs) represents one of the most promising methods for future large-scale power production from renewable energy sources [1][2][3][4][5][6][7][8][9][10][11][12][13]. In these cells the sensitizer is one of the key components, harvesting the solar radiation and converting it to electric current.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of sunlight to electricity using dye-sensitized solar cells (DSCs) represents one of the most promising methods for future large-scale power production from renewable energy sources [1][2][3][4][5][6][7][8][9][10][11][12][13]. In these cells the sensitizer is one of the key components, harvesting the solar radiation and converting it to electric current.…”
Section: Introductionmentioning
confidence: 99%
“…1 H and 13 C NMR spectra were measured on a Bruker 200 MHz spectrometer. The reported chemical shifts were in PPM against TMS.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the scale up of DSC devices over large area for industrial and commercial purpose, poses some scientific and technological challenges. In particular, it is important to mention the reduction of the series resistance (Dai et al, 2005), strictly related to the increasing of the performance, stability and working life time of large area modules (P. Wang et al, 2003;Sommeling et al, 2004;Kuang et al, 2007), and the setting-up of a highly automated and energetically efficient fabrication process (Somani et al, 2005;Meyer et al, 2007;Mincuzzi et al, 2009). …”
Section: Large Area Devicesmentioning
confidence: 99%
“…It has been considered with particular attention to some organic dyes having complementary spectral response in the red with respect to the ruthenium-based dyes (largely used for standard DSC), such as squaraine (SQ1) (Clifford et al, 2004), cyanine (Pandey et al, 2010), phthalocyanine (Ono et al, 2009), hemicyanine (Cid et al, 2007). Indeed in other studies the co-sensibilization approach has shown high device performances toward red and violet as well in the electromagnetic spectrum (Yao et al, 2003;Kuang et al, 2007;Yum et al, 2007Yum et al, , 2008Clifford et al, 2004). The scope of co-sensitization is to enlarge the absorbance spectrum of the cell toward the Near Infra Red (NIR), thus to increase the Incident Photon to Current Efficiency (IPCE) by enhancing the LHE (Light Harvesting Efficiency) and the efficiency of injection inside the TiO 2 (see IPCE section).…”
Section: Co-sensitizationmentioning
confidence: 99%
“…Many co-sensitization systems have been proposed and demonstrated improved photovoltaic performance, such as ruthenium complex co-sensitized with an organic dye, 17-26 porphyrin 27-30 or phtalocyanine [31][32][33][34] co-sensitized with an organic dye, and organic dye co-sensitized with another organic dye. [35][36][37][38][39][40] The co-sensitizers generally have a suitable molecular structure to avoid competitive adsorption and effectively suppress dye aggregation.…”
Section: Introductionmentioning
confidence: 99%